Protein S mRNA in Patients with Protein S Deficiency - Sacchi, E; Pinotti, M; Marchetti, G; Merati, G; Tagliabue, L; Mannucci, P M; Bernardi, F (Thrombosis and Haemostasis, 1995)
A protein S gene polymorphism, detectable by restriction analysis (BstXI) of amplified exonic sequences (exon 15), was studied in seven Italian families with protein S deficiency. In the 17 individuals heterozygous for the polymorphism the study was extended to platelet mRNA through reverse transcription, amplification and densitometric analysis. mRNA produced by the putative defective protein S genes was absent in three families and reduced to a different extent (as expressed by altered allelic ratios) in four families. The allelic ratios helped to distinguish total protein S deficiency (type I) from free protein S deficiency (type IIa) in families with equivocal phenotypes. This study indicates that the study of platelet mRNA, in association with phenotypic analysis based upon protein S assays in plasma, helps to classify patients with protein S deficiency.